Visible‐Light‐Driven Cleavage of C−O Linkage for Lignin Valorization to Functionalized Aromatics. Issue 22 (22nd October 2019) - Lin, Jinchi; Wu, Xuejiao; Xie, Shunji; Chen, Liangyi; Zhang, Qinghong; Deng, Weiping; Wang, Ye
Abstract: Lignin is the most abundant source of renewable aromatics. Catalytic valorization of lignin into functionalized aromatics is attractive but challenging. Photocatalysis is a promising sustainable approach. The strategies for designing well‐performing photocatalysts are desired but remain limited. Herein, a facile energy band engineering strategy for promoting the photocatalytic activity of zinc–indium–sulfide (Zn m In2 S m +3 ) for cleavage of the lignol β‐O‐4 bond under mild conditions was developed. The energy band structure of Zn m In2 S m +3 could be tuned by controlling the atomic ratio of Zn/In. It was found that Zn4 In2 S7 performed best for cleavage of the β‐O‐4 bond under visible‐light irradiation, owing to its appropriate energy band structure for offering adequate visible‐light absorption and suitable redox capability. Functionalized aromatic monomers with near 18.4 wt % yield could be obtained from organosolv birch lignin. Mechanistic studies revealed that the β‐O‐4 bond was efficiently cleaved mainly through a one‐step redox‐neutral pathway via a Cα radical intermediate. The thiol groups on the surface of Zn4 In2 S7 played a key role in cleavage of the β‐O‐4 bond. Abstract : Energy band engineering : Efficient photocatalytic depolymerization of lignin to functionalized aromatic monomers over zinc–indium–sulfide catalysts through an energy band engineering strategy is reported. The energy band structure of Zn m In2 S m +3 can be tuned by controlling the atomic ratio of Zn/In to find the best catalyst for cleavage of the β‐O‐4 bond under visible‐light irradiation.